2012
DOI: 10.1021/cs3006204
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of the Water–Gas Shift Reaction over Pt/CexZr1–xO2 Catalysts: The Effect of Pt Particle Size and Zr Dopant

Abstract: A series of y wt % Pt/Ce x Zr1–x O2 catalysts (y = 0.1, 0.5, and 1.0; x = 0.3, 0.5, and 0.7) were synthesized and characterized to investigate the effect of CeO2 doping with Zr4+ and of Pt particle size (Pt/Ce0.5Zr0.5O2) on important mechanistic and kinetic aspects of the water–gas shift (WGS) reaction. These included the concentration (μmol·g–1 or θ (surface coverage based on Pts)) and chemical structure of active reaction intermediates present in the “carbon path” and “hydrogen path” of the WGS reaction in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
101
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 98 publications
9
101
0
Order By: Relevance
“…Such a mechanism was first proposed by Verykios and his co-workers [47,48] over Ni/La 2 O 3 . One of the important kinetic parameters in this bi-functional mechanism is the concentration of catalytic sites along the Ni-support interface, fact that makes more appropriate the estimation of intrinsic kinetic rates in terms of mol cm −1 s −1 and not in terms of TOF (s −1 ) (based on the metal surface), as recently reported for the WGS reaction on Pt supported on similar Ce 1−x M x O 2−ı (M = Zr 4+ , Ti 4+ , La 3+ ) carriers [49,50].…”
Section: Catalytic Performance Of Nimentioning
confidence: 99%
“…Such a mechanism was first proposed by Verykios and his co-workers [47,48] over Ni/La 2 O 3 . One of the important kinetic parameters in this bi-functional mechanism is the concentration of catalytic sites along the Ni-support interface, fact that makes more appropriate the estimation of intrinsic kinetic rates in terms of mol cm −1 s −1 and not in terms of TOF (s −1 ) (based on the metal surface), as recently reported for the WGS reaction on Pt supported on similar Ce 1−x M x O 2−ı (M = Zr 4+ , Ti 4+ , La 3+ ) carriers [49,50].…”
Section: Catalytic Performance Of Nimentioning
confidence: 99%
“…2 and can be ascribed to carbonated species adsorbed onto ceria surface, such as formate, carboxylate, and carbonate species [17,19,20,47]. The bands around 1600 and 1360 cm À1 are mostly likely indicative of formate species; however, it was not possible to confirm them, because there were no bands in the region of 2500-3000 cm À1 that were due to C-H stretching [17,19]. These complementary bands may be difficult to identify because the surface area of the supports is low.…”
Section: Catalystmentioning
confidence: 99%
“…In the search for more advantageous catalysts for the WGSR, several studies with noble metal catalysts have been reported [9][10][11][12][13][14][15][16][17][18][19][20][21]. The use of noble metal catalysts is related to their capability of being stable in an oxidizing atmosphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12] In particular, the shape and size control of the noble metal catalysts have been proved to signicantly affect the catalytic performance. 13,14 For example, the activation energies for the electron-transfer reaction between Fe(CN) 6 3À and S 2 O 3 2À has been determined to be effectively tailored by the shape of the Pt nanoparticles from tetrahedral to cubic to spherical.…”
mentioning
confidence: 99%